Maternal Stress and family resilience with regard to congenital heart disease in children. - Vijayan, Vidya (Journal of Social Work Education and Practice, 2017)
Parenting is one of the challenging jobs an individual will ever face. Childhood illnesses rudely shatter the sensibilities. Congenital malformations and in particular congenital heart diseases are likely to become important contributors to infant mortality. The objective of the study is to assess the stress levels among mothers of children with congenital heart disease and to study the resilience among families of children with congenital heart disease. Mothers of children who have congenital heart disease and those who come to the hospital for follow up visit in the outpatient department and who fulfills the criteria of inclusion. 50 mothers (n=50) were randomly chosen for the study. The Parenting Stress Index-Short Form (PSI-SF) (Abidin, 1995) is a 36 item scale used to measure maternal stress. Family resilience was assessed using the Family Resilience Assessment Scale (FRAS) developed by Tucker Sixbey (2005). A significant negative correlation was found between the family resilience (FRAS) and parental stress. This relationship suggests that as the family resilience increases, parental stress in mother decreases. The family resilience seems to have a good effect in reducing the parental stress.
Keywords: Maternal stress; Congenital heart disease; Family; Resilience; Children; Parents; Parenting distress; Social work